A magnitude do efeito da idade relativa no futsal - Oldemar Mazzardo; Bryan S. Jacob; Thiago G. L. Dognini; Wagner de Campos (Universidade Estadual do Oeste do Paraná, 2016)
The objectives of this study were to verify the existence and magnitude of RAE in indoor soccer athletes by categories; to identify if the RAE associates with playing position; and to verify if there are differences in the EIR association with team´s rankings based on the last championship. The sample consisted of 978 brazilian indoor soccer players of the Under 15, Under 17 and Under 20 categories who participated, respectively, in the eighteenth (2011), seventh (2012) and thirtieth (2012) Brazil Futsal Cup; and the athletes of the Adult category of the Futsal League, 2011. At the end of the championship, the birthdate, categories, teams and positions of the players, and final classification at the tournament were collected in the individual report of each team. The athletes were distributed in quartiles based on their birthdates. The data analysis investigated the distributions of the observed and expected values through the Chi-square test with significance level of p<0.05, and in the multiple comparison analyzes using the Bonferroni correction with the level of significance of p<0.0083. Contingency Coefficient and Kruskall-Wallis test were also performed to investigate differences in RAE between the best and the worst ranked teams. The RAE is present in futsal athletes in general and in the Under 15, Under 17 and Adult categories. Moreover, the RAE was significantly associated with all playing positions with effect sizes ranging from small to medium. Finally, there were no significant differences between the best and worst ranked in the Under 15 and Adult categories. The RAE is observed in indoor soccer athletes in minor leagues and professional teams independent of the position of players or team' ranking